Climate change and trade on the road to Copenhagen ICTSD global platform on climate change, trade policies and sustainable energy - International Centre for Trade and Sustainable Development (Geneva, Switzerland ICTSD International Centre for Trade and Sustainable Development, 2008)
The global effort to address climate change will require a fundamental transformation of our economies and the ways we use energy. The current phase of negotiations under the UN Framework Convention on Climate Change (UNFCCC) is set to lay the groundwork for the necessary policy reform, and will require concerted and cooperative efforts by individual countries, the business sector and civil society. Innovation ? both with regard to the technologies of the future and the regulatory frameworks used to usher them in at the scale needed ? will be key to success.
This document raises the debate on climate change and trade policies as either friends or foes. The approach adopted in this paper takes climate change as the entry point. It frames the discussion within the five pillars of the Bali Road Map: i) the long-term vision, ii) mitigation of climate change, iii) adaptation to climate change, iv) technology and v) financing. The paper examines the various trade and climate change policy interlinkages with a view to identifying a positive agenda for trade and trade policies to contribute to a successful global climate change agreement and its implementation.
Unpacking the trade and climate change linkages -- Mitigation -- Adaptation -- Technological development, innovation and dissemination -- Financing and investment: trade related implications.
"December 2008."
"Policy discussion paper."
Includes bibliographical references (p. 47-52)
Keywords: Climate change mitigation -- Copenhagen; Climatic changes -- Copenhagen